Trends and Emerging Themes in Social Media Research within Digital Sociology: A Bibliometric Review (2014–2024) - Musa M Juwara; Helen Dian Fridayani (Universitas Muhammadiyah Ponorogo, 2027)
As Information and Communications Technologies (ICTs) become increasingly relevant and advanced, resulting in the emergence of new subfields, this study presents a bibliometric analysis of digital sociology from 2014 to 2024, with a focus on social media research within the field of sociology. Given the growing influence of digital technologies on social institutions and interactions, this study seeks to examine emerging trends and themes. We utilised data from the Scopus database to examine 227 documents on digital sociology, including annual publication trends, leading countries, affiliations, journals, and authors. Additionally, it analysed the co-citation network by authors, journals, and keywords. The findings revealed a steady increase in publications with an annual average of approximately 10%. It identified major themes surrounding digital sociology, including digital identity, online activism and algorithms and data exposure. It highlights an inclination toward the ethical and societal consequences of digital engagement. The study’s novelty lies within the intersection between digital sociology and social media research outcomes, which is specific and timely. The study offers a comprehensive understanding of digital sociology and its thematic developments over the past decade, laying the groundwork for future research by identifying gaps and areas of interest. However, limitations include a heavy reliance on a single database and English-language sources. Future studies could focus on the evolving dynamics of trends and themes, with broader regional engagement to widen discourse in digital sociology globally. Keywords: Social Media Online; Platforms Digital; Communication; Digital Sociology;